Shaped by stories : the ethical power of narratives - Gregory, Marshall W., 1940-2012 (University of Notre Dame Press, 2009)
Marshall Gregory begins with the premise that our lives are saturated with stories, ranging from magazines, books, films, television, and blogs to the words spoken by politicians, pastors, and teachers. He then explores the ethical implications of this universal human obsession with narratives.--From publisher description.